SEKURITISASI PMI DOMESTIC WORKER DI MALAYSIA TAHUN 2017-2020 - Agung Prija Utama (Global Mind, 2022)
This essay highlights the problem of Indonesian Migrant Workers in Malaysia by using securitization theory regarding migrant workers in obtaining human rights and examines whether the policies imposed in Malaysia for domestic workers aimed at that have been implemented properly as a concentration of human security. The paper is reviewed by elaborating the literature on foreign workers in Malaysia along with the conditions and policies regarding the restriction of some rights of domestic workers will be described and analyzed under the human rights and government regulations of the two countries in dealing with migrant workers.